Active human immunodeficiency virus protease is required for viral infectivity. - Kohl, N E (1988)
Retroviral proteins are synthesized as polyprotein precursors that undergo proteolytic cleavages to yield the mature viral proteins. The role of the human immunodeficiency virus (HIV) protease in the viral replication cycle was examined by use of a site-directed mutation in the protease gene. The HIV protease gene product was expressed in Escherichia coli and observed to cleave HIV gag p55 to gag p24 and gag p17 in vitro. Substitution of aspartic acid residue 25 (Asp-25) of this protein with an asparagine residue did not affect the expression of the protein, but it eliminated detectable in vitro proteolytic activity against HIV gag p55. A mutant HIV provirus was constructed that contained the Asn-25 mutation within the protease gene. SW480 human colon carcinoma cells transfected with the Asn-25 mutant proviral DNA produced virions that contained gag p55 but not gag p24, whereas virions from cells transfected with the wild-type DNA contained both gag p55 and gag p24. The mutant virions were not able to infect MT-4 lymphoid cells. In contrast, these cells were highly sensitive to infection by the wild-type virions. These results demonstrate that the HIV protease is an essential viral enzyme and, consequently, an attractive target for anti-HIV drugs.